ASSESSMENT OF WIND ENERGY POTENTIAL FOR ACCRA, GHANA USING TWO PARAMETER WEIBULL DISTRIBUTION FUNCTION - Akpootu, Davidson Odafe; Fagbemi, Samuel Adesina (FUDMA JOURNAL OF SCIENCES, 2022)
This study investigates the predictive ability of two-parameter Weibull distribution function for Accra, Ghana using fifteen years (2002 â€“ 2016) meteorological parameter of monthly mean wind speed data. The monthly and annual averaged wind speed was estimated to be . The annual mean values of the maximum energy â€“ carrying wind speed and most probable wind speed were found to be  and  respectively. The two parameters of the Weibull statistics found in this study for Accra were within the range  for the shape parameters and  for the scale parameters. The results of the wind power density indicated that the location has a good prospect for wind power generation with the highest value of  found in September, 2006. The linear relationship between the monthly mean wind power density and mean wind speed shows that a perfect correlation with coefficient of correlation of 99.3 % exists between them. The results obtained from this study revealed that the Weibull function was found appropriate for analyzing measured wind speed data and in predicting the wind power density for the region under investigation. Therefore, Accra has an excellent prospect for wind power generation
Keywords: wind power generation, weibull distribution function, coefficient of correlation, wind power density, Accra.